Proposta de uma metodologia de apoio à tomada de decisão para a localização de centros de distribuição no setor varejista de móveis e eletrodomésticos - Spak, Marcia Danieli Szeremeta (2012)
The retail sector of furniture and appliances is in expansion and is directly affected by market competitiveness. The Companies in this sector are constantly seeking reduction of prices and delivery times of products, to maintain their position before competitors. One of the factors that directly influence the competitiveness of these organizations are the high costs of the distribution system. In order to reduce the impacts on the distribution system, the present study aimed to propose a model to support decision making for the location of distribution centers in the retail sector of furniture and appliances. The work divided into three stages for its conception. In the first stage was used a non-linear programming model to define an optimal point in the region covered in the study and subsequently been identified five cities around that optimal point. The second stage was composed by defining criteria and sub-criteria that influence the decision, and the application of AHP method for selecting the best city for installing the distribution center. In the third stage is sought to identify the best ground among three alternatives, that been evaluated by AHP method from the definition of criteria and sub-criteria directed this decision context. The result show that the factor transport and market are mainly responsible for choosing the city, and the installation and accessibility to the location of the ground. The study identified the alternative Arapongas as the best city and the ground 3 as the best place to install the distribution center.